2001
DOI: 10.1007/s002100000381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated systemic administration of d -Fenfluramine on serotonin and glutamate release in rat ventral hippocampus: comparison with methamphetamine using in vivo microdialysis

Abstract: We compared the effects of three systemic injections of various doses of d-Fenfluramine, an indirect serotonergic agonist (1.3, 5 or 10 mg/kg), to those of a known neurotoxin, methamphetamine (METH, at a 7.5 mg/kg dose), given i.p. at 2-h intervals, simultaneously on extracellular levels of glutamate [Gluext] and 5-HT [5-HText] in the ventral hippocampus (VHPC) using in vivo microdialysis in conscious rats. METH markedly increased both [Gluext] (+77% over the control value in saline-treated rats) and [5-HText]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…Adult and adolescent rats were injected with either saline or fenfluramine (2 mg/kg) 30 minutes prior to testing (n=12 per age, per treatment). This dose of fenfluramine was expected to be non-maximal in terms of increasing extracellular serotonin in the brain (Gundlah et al, 1997; Rocher and Gardier, 2001; Tao et al, 2002). For each age group, saline-treated animals were used as a control group to determine baseline behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Adult and adolescent rats were injected with either saline or fenfluramine (2 mg/kg) 30 minutes prior to testing (n=12 per age, per treatment). This dose of fenfluramine was expected to be non-maximal in terms of increasing extracellular serotonin in the brain (Gundlah et al, 1997; Rocher and Gardier, 2001; Tao et al, 2002). For each age group, saline-treated animals were used as a control group to determine baseline behavior.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to increases in both DA and 5HT, amphetamine-related drugs of abuse also increase extracellular levels of glutamate in both the striatum and hippocampus (Rocher and Gardier 2001; Nash and Yamamoto 1992; Cunningham et al 2004). Despite the actions of METH and MDMA at DAT and SERT, there is no indication that increases in glutamate are mediated by a direct interaction with the plasmalemmal glutamate transporter (Kokoshka et al 1998).…”
Section: Basic Neuropharmacology Of Meth and Mdmamentioning
confidence: 99%
“…It has been shown that repeated high dose treatment with MA (10 mg/kg every 2 hrs × 4) can lead to damage of dopaminergic terminals and increases of extracellular glutamate concentration (Thomas et al, 2004; Halpin et al, 2013; Bowyer et al, 1994). In addition, studies reported that repeated MA exposure can lead to increase in both extracellular concentrations of dopamine and glutamate in the striatum (Nash and Yamamoto, 1992) and hippocampus (Rocher and Gardier, 2001). Although, it is now well known about the effects of MA exposure in the increase of extracellular glutamate in specific brain regions, there is little known about its effects on glutamate transporters after MA administration or MA administered sequentially with EtOH.…”
Section: Introductionmentioning
confidence: 99%